Trocar-site evisceration of the vermiform appendix following laparoscopic sigmoid colectomy: A case report. (2017) - Bhangu, Jagdeep Singh; Exner, Ruth; Bachleitner-Hofmann, Thomas
Highlights: Trocar-site evisceration of the vermiform appendix following laparoscopic surgery is a rare complication. A regular intraoperative appearance of the vermiform appendix does not reliably rule out the presence of a diseased appendix. Incidental appendectomy should be considered in all patients undergoing colorectal surgery. The restrictive use of prophylactic drains after colorectal procedures is recommended. Abstract: Introduction: There is an ongoing debate whether prophylactic drainage or incidental appendectomy should be performed in patients undergoing colorectal surgery. On the other hand, it has been shown that the placement of drains through former trocar sites as well as the use of large (≥10 mm) trocars, incomplete fascial closure or closed laparoscopy technique all predispose for the occurrence of trocar site hernias. Presentation of case: We report the case of a 59-year-old male patient who underwent laparoscopic sigmoid colectomy with primary anastomosis for recurrent sigmoid diverticulitis. Preoperative diagnostics revealed no abnormalities other than multiple diverticula in the sigmoid colon. The subsequent surgery was conducted without any complications. Due to inconspicuous intraoperative appearance of the vermiform appendix, no incidental appendectomy was performed. On the 4th postoperative day, the Easy Flow drain − which had been placed prophylactically through the 12 mm trocar site in the right lower abdomen − was removed. Four hours after drain removal, trocar-site evisceration of the vermiform appendix occurred, requiring emergency surgery. Discussion and conclusion: The present case is yet another argument for restricting the use of prophylactic drains in colorectal surgery as well as closing port sites of ≥10 mm diameter. Furthermore, incidental appendectomy may be considered since it is able to prevent this type of complication and can be performed with minimal cost and morbidity.